Wood-polymer composites in moving bed technology - Kruszelnicka, I.; Ginter-Kramarczyk, D.; Michałkiewicz, M.; Kloziński, A.; Zajchowski, S.; Jakubowska, P.; Tomaszewska, J. (Polimery, 2014)
Modern water treatment technology utilizing the Moving Bed Biofilm Reactor (MBBR) is based on the principle of a biological membrane — so-called biofilm — growing on the specially designed plastic parts that are immersed in the entire volume of the reactor. Currently, moving bed biofilters made solely of polymeric materials, among others polyethylene and polypropylene, are used in wastewater treatment. Wood-polymer composites (WPC) are an innovative solution in this field. In the present study, poly(vinyl chloride) was examined as a matrix of polymer-wood composites and wood chips (used on an industrial scale for the production of chipboards) as a filler. The effect of prolonged exposure to the microorganisms of activated sludge, with well-known technical and technological parameters, on the mechanical properties of composites was determined. A quantitative and qualitative analysis of newly formed biofilms was carried out. The study showed a direct effect of the filler and its particle size on the modulus of elasticity of composites as well as on the susceptibility of their surfaces to the formation of biofilm. These preliminary studies have demonstrated the applicability of WPC with PVC matrix as a material in the manufacture of substrates for biological membranes in the MBBR method.